The Influence Of Service Quality And Price Perceptions On Customer Loyalty And Customer Satisfaction As Intervening Variables - Sujana, Sujana; Yusni, Yusni (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to determine whether: 1) to determine the effect of service quality on JNE customer satisfaction, 2) to determine the effect of perceived price on customer satisfaction in JNE, 3) to determine the effect of service quality on customer loyalty in JNE , 4) to determine the effect Price perceptions on customer loyalty at JNE, 5) to determine the effect of customer satisfaction on customer loyalty at JNE, 6) to determine the effect of service quality on customer loyalty with customer satisfaction as the intervening variable, 7) to determine the effect of price perceptions on customer loyalty and customer satisfaction as an intervening variable. This type of research is quantitative. The population in this research is all customers who have used the delivery service of PT Tiki Jalan Nugraha Ekakurir (JNE), with a sample of 200 respondents. The sampling procedure used in this study was non-probability with a purposive sampling technique which is a sampling technique based on the evaluation of the respondent's knowledge regarding the object of research by the researcher. The data collection technique in this study was a questionnaire. The method used in this research is Structural Equation Modeling which is processed using the AMOS 23 program. The research results are 1) Service quality has a positive and significant effect on customer satisfaction, 2) Price perception has a positive and significant effect on customer satisfaction, 3) Service quality has a positive and significant effect on customer loyalty, 4) Price perception has a negative and insignificant effect on customer loyalty satisfaction, 5) customer satisfaction has a positive and significant effect on customer loyalty, 6) service quality has a positive and significant effect on customer loyalty not mediated by customer satisfaction and 7) price perception has a negative and insignificant effect on customer loyalty through mediation of customer satisfaction. Keywords: Service Quality, Perceived Price, Customer Satisfaction and Customer Loyalty